2016
DOI: 10.1080/17290376.2016.1197146
|View full text |Cite
|
Sign up to set email alerts
|

How peer conversations about HIV/AIDS media messages affect comprehension and beliefs of young South African women

Abstract: Most existent research on the effects of interpersonal discussions about health campaign messages is based on surveys. In this study, we analysed actual conversations about an HIV/AIDS poster to find out possible effects. Young South African women in 59 dyads (n = 118) participated in conversations about a deliberately puzzling HIV and AIDS poster that cautioned the target group to be faithful to one sexual partner. We measured their comprehension of the poster and beliefs about the message, before and after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Two more outcome variables were measured: attitude and intention to speak to a friend or family member who is involved with crystal meth about their drug habit. As argued in Lubinga, Maes, and Jansen (2016), for example, the efficacy of mass media health communication campaigns can be enhanced by conversations about the core messages of these campaigns (see also Donn e, Jansen, & Hoeks, 2017; Duggan, 2006;Southwell & Yzer, 2007). Such conversations about health messages may lead to changes in relevant beliefs (Hwang, 2012), attitudes (Hendriks, Van den Putte, & De Bruijn, 2014), social norms (Chatterjee, Bhanot, Frank, Murphy, & Power, 2009), and behavioral intentions (Van den Putte, Yzer, Southwell, De Bruijn, & Willemsen, 2011), thus fostering behavior change.…”
Section: Attitudes and Intentionsmentioning
confidence: 89%
“…Two more outcome variables were measured: attitude and intention to speak to a friend or family member who is involved with crystal meth about their drug habit. As argued in Lubinga, Maes, and Jansen (2016), for example, the efficacy of mass media health communication campaigns can be enhanced by conversations about the core messages of these campaigns (see also Donn e, Jansen, & Hoeks, 2017; Duggan, 2006;Southwell & Yzer, 2007). Such conversations about health messages may lead to changes in relevant beliefs (Hwang, 2012), attitudes (Hendriks, Van den Putte, & De Bruijn, 2014), social norms (Chatterjee, Bhanot, Frank, Murphy, & Power, 2009), and behavioral intentions (Van den Putte, Yzer, Southwell, De Bruijn, & Willemsen, 2011), thus fostering behavior change.…”
Section: Attitudes and Intentionsmentioning
confidence: 89%
“…The dependent variables we used included attitudes and intentions related to the socially responsible behaviour of not using MA, as well as speaking to a friend or family member who is involved with MA about their drug habit. As Davis and Jansen [ 11 ] argued, referring to Lubinga and colleagues [ 41 ], among others, the efficacy of mass media health communication campaigns can be enhanced by conversations about the core messages of these campaigns. Such conversations may lead to changes in relevant beliefs, attitudes, social norms, and behavioural intentions [ 42 , 43 , 44 , 45 ], thus fostering behaviour change.…”
Section: Methodsmentioning
confidence: 99%
“…Focusing on the mechanism underlying the effectiveness of interpersonal communication seems especially important as conversations that are stimulated by a health campaign will not always be in agreement with the aims of the campaign (Hafstad & Aaro, 1997;Dunlop, 2011). Indeed, several studies have found unintended -and undesirable-effects of conversations about health messages (David, Capella, and Fishbein, 2006;Van den Putte et al, 2011;Hendriks, Van den Putte, De Bruijn, & De Vreese, 2014;Lubinga, Maes, & Jansen, 2016). Lubinga et al (2016), for instance, found that young South African adolescents' conversations about cryptic HIV/AIDS messages decreased the level of understanding of these health messages in a considerable number of cases.…”
Section: 1the Role Of Interpersonal Health Communication In the Permentioning
confidence: 99%
“…Indeed, several studies have found unintended -and undesirable-effects of conversations about health messages (David, Capella, and Fishbein, 2006;Van den Putte et al, 2011;Hendriks, Van den Putte, De Bruijn, & De Vreese, 2014;Lubinga, Maes, & Jansen, 2016). Lubinga et al (2016), for instance, found that young South African adolescents' conversations about cryptic HIV/AIDS messages decreased the level of understanding of these health messages in a considerable number of cases.…”
Section: 1the Role Of Interpersonal Health Communication In the Permentioning
confidence: 99%
See 1 more Smart Citation